Credit expansion and development – A Schumpeterian and Keynesian view of the Chinese miracle - Hansjörg Herr (Intervention. European Journal of Economics and Economic Policies, 2010)
In neoclassical thinking, insufficient development is considered the result of a lack of resources, and an inefficient allocation. Deregulated markets have to guarantee a better allocation of resources as well as a net resource inflow to augment the domestic physical capital stock. From a Schumpeterian-Keynesian perspective, it is not the lack of physical resources and optimal allocation which prevent development. It is first and foremost the lack of a sufficient credit-investment mechanism which leads to the perpetuation of underdevelopment. It is shown here that the Schumpeterian-Keynesian perspective gives a much more plausible interpretation of the Chinese development than the neoclassical perspective. It is also shown under which regulations and conditions a credit-investment process in developing countries is possible.
Keywords: E12; E44; F36; F43; 330; credit; economic development; Schumpeter; Keynes; China